Sustainable Agriculture in Relation to Problems of Soil Degradation and How to Amend Such Soils for Optimum Crop Production in Nigeria - Usman, M.; Ibrahim, F.; Oyetola, S. O. (International Journal For Research In Agricultural And Food Science, 2018)
The importance of soil degradation among global issues is being enhanced because of its impact on world food security and quality of the environment. It is a key issue that affects soil productivity and environmental sustainability. Soil degradation implies a decline in soil quality. It is a global problem that is more severe in the tropics and sub-tropics. In addition to negatively impacting agronomic production, soil degradation can also dampen economic growth, especially in countries where agriculture is the engine for economic development. However, restoring the quality of degraded soils is a challenging task, especially in countries dominated by small, resource-poor landholders like Nigeria. The focus of this paper is on sustainable agriculture in relation to problems of soil degradation and how to amend degraded soils for optimum production. The paper examined various types of soil degradation, their causes and adopted policies in various phases for the curtailment of soil degradation with the hope that this will further enhance the development of agriculture, with the expectation that development of agriculture is the major source of livelihood for a larger percentage of the populace of developing nations including Nigeria.